2014
DOI: 10.1371/journal.pone.0105188
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hydrogen Peroxide Accumulation and Toxicity by a Catalase from Mycoplasma iowae

Abstract: Mycoplasma iowae is a well-established avian pathogen that can infect and damage many sites throughout the body. One potential mediator of cellular damage by mycoplasmas is the production of H2O2 via a glycerol catabolic pathway whose genes are widespread amongst many mycoplasma species. Previous sequencing of M. iowae serovar I strain 695 revealed the presence of not only genes for H2O2 production through glycerol catabolism but also the first documented mycoplasma gene for catalase, which degrades H2O2. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…in riboflavin synthase of CML. Instead, virulence factors were absent in the CML, but common to other pathogens (Glass et al, 2000;Kannan and Baseman, 2006;Szczepanek et al, 2010;Indikova et al, 2013;Kokkayil and Dhawan, 2015) and genes involved in the generation of H 2 O 2 , which is a major mediator for Mycoplasma pathogens to cause cellular damage (Pritchard et al, 2014), were also absent in the CML. All these results indicated that "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…in riboflavin synthase of CML. Instead, virulence factors were absent in the CML, but common to other pathogens (Glass et al, 2000;Kannan and Baseman, 2006;Szczepanek et al, 2010;Indikova et al, 2013;Kokkayil and Dhawan, 2015) and genes involved in the generation of H 2 O 2 , which is a major mediator for Mycoplasma pathogens to cause cellular damage (Pritchard et al, 2014), were also absent in the CML. All these results indicated that "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of enzymes of M. genitalium that control the damage done by reactive oxygen species, such as peptide methionine sulfoxide reductase (166), organic hydroperoxide reductase (167), and hydroperoxide peroxidase (168), have been described. However, direct reduction of hydrogen peroxide by catalase among mycoplasmas is described only in Mycoplasma iowae (169). The fact that M. gallisepticum engineered to produce catalase is strongly attenuated for toxicity in the invertebrate animal model Caenorhabditis elegans (169, 170) not only underscores the pathogenic value of reactive oxygen species but also might explain the absence of catalase in M. pneumoniae.…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…MYPE1530, MYPE1550, MYPE1560, and MYPE1570. Together with MYPE4000, they shared no specific sequence homology with other proteins except in a close relative of M. penetrans, namely, Mycoplasma iowae (25); however, the first four were labeled as predicted cytoskeletal proteins in the original annotation of the M. penetrans genome, on the basis of predicted extensive ␣-helical coiled-coil structures, reminiscent of Mycoplasma pneumoniae AO protein HMW2 (14), which is predicted to constitute a major structural element within the M. pneumoniae AO cytoskeleton (26)(27)(28). The absence of sequence homology of these five proteins to the proteins of the AO cytoskeleton of M. pneumoniae (28) or the analogous structure in M. mobile (29), together with the disparity in the detergent-insoluble structures between M. penetrans and mycoplasmas from other phylogenetic clusters, is consistent with a model in which attachment organelles arose independently multiple times during the course of mycoplasma evolution (7,30).…”
Section: Resultsmentioning
confidence: 99%